Gender Equity in Jordanian Higher Education System: Yarmouk University as a Case Study - Mahasneh, Anjad; Al-Muhaisen, Batoul (Dirasat: Human and Social Sciences, 2019)
The purpose of this study is to investigate practices of gender equity in relation to women in Jordanian higher education system, specifically in the case of Yarmouk University. Despite the progress that has been made at raising awareness of gender-related issues in different areas, especially education, and due to the decline of Jordan’s rank on world gender index, more efforts are still needed to increase participation of women in the educational sector in Jordan. In this evaluation study, quantitative data have been collected through a questionnaire consisting of 29 closed-ended items that has been distributed to female academics at Yarmouk University. Descriptive statistics, Pearson correlation, and Kruskal–Wallis analysis are used to analyze the data. The results reveal that most of female academics at Yarmouk University agree that gender equity is neither widely available nor well practiced at the university. Furthermore, gender equity is not part of the university policies, documents or regulations. Therefore, more integration of female instructors is needed, especially in senior positions.